2i+(x+yi)=6whatisx+yi

Simple and best practice solution for 2i+(x+yi)=6whatisx+yi equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2i+(x+yi)=6whatisx+yi equation:


Simplifying
2i + (x + yi) = 6whatisx + yi

Reorder the terms:
2i + (iy + x) = 6whatisx + yi

Remove parenthesis around (iy + x)
2i + iy + x = 6whatisx + yi

Add '-1iy' to each side of the equation.
2i + iy + -1iy + x = 6ahistwx + iy + -1iy

Combine like terms: iy + -1iy = 0
2i + 0 + x = 6ahistwx + iy + -1iy
2i + x = 6ahistwx + iy + -1iy

Combine like terms: iy + -1iy = 0
2i + x = 6ahistwx + 0
2i + x = 6ahistwx

Solving
2i + x = 6ahistwx

Solving for variable 'i'.

Move all terms containing i to the left, all other terms to the right.

Add '-6ahistwx' to each side of the equation.
2i + -6ahistwx + x = 6ahistwx + -6ahistwx

Reorder the terms:
-6ahistwx + 2i + x = 6ahistwx + -6ahistwx

Combine like terms: 6ahistwx + -6ahistwx = 0
-6ahistwx + 2i + x = 0

Add '-1x' to each side of the equation.
-6ahistwx + 2i + x + -1x = 0 + -1x

Combine like terms: x + -1x = 0
-6ahistwx + 2i + 0 = 0 + -1x
-6ahistwx + 2i = 0 + -1x
Remove the zero:
-6ahistwx + 2i = -1x

Combine like terms: -1x + x = 0
-6ahistwx + 2i + x = 0

The solution to this equation could not be determined.

See similar equations:

| 2x+6x+10=90 | | x+15=7.6 | | 8(4+y)+4y=3 | | 78/42 | | 8(x-4)-3=6x+1 | | -6(x+2)-16=19+7 | | 7k+19=5 | | 8x-2=6x+5 | | m=6n+8 | | x+x-.66=30 | | X^2-2/3=30 | | 9x^2-5x-1= | | 91=6(12+b) | | 25-x÷2=x/3 | | 5/42x=-6/42 | | 2b-3b= | | 5/42=-6/42 | | 9x-5=7x+29 | | -5(3x-4)= | | 25c^2+20ct+4t^2=0 | | 5x+6=3x+34 | | 48v^2-120v+75=0 | | 5x+7=3x+49 | | 2x+4x+60=180 | | 100c^2-120c+36=0 | | 6x-18=-126 | | (-1/3)2 | | 5x+60+10x=180 | | 8x+3=6y-8 | | 3(y-6)-5y=-8 | | 42sqrt(4*2/41xsqrt00.125*x | | 8y/2 |

Equations solver categories